Influencia de la concentración de thiourea sobre la extracción de oro por lixiviacion de un mineral oxidado a pH ácido controlado con ácido cítrico - Peña Ulloa, Irwin Justo (2016)
This research allowed us to evaluate the behavior of an oxidized ore from the Cerro El Toro – Huamachuco -Province of Sanchez Carrion-La Libertad, using thiourea as an effective alternative that replaces a1 cyanide leaching gold, justifying this research to minimize environmental pollution and increase the percentage of gold extraction or maintain cyanide obtained, but with the advantage of rapid dissolution rate under leaching times and especially controlled acid pH with citric acid (C₆H₈O₇) and this Finally an organic acid which replaces sulfuric acid (H₂SO₄) in a normal process of leaching. The particle size of the oxidized ore was 100% solids and mesh # 200 and the tests were performed in the laboratory mineral processing metallurgical engineering department at the National University of Trujillo. In the experimental part, tests were performed on the electric agitator, which got to roll (rotate) to leach for a period of 4 to 5 hours and then perform corrections thiourea, every 30 minutes until the consumption of thiourea is almost nil. The chemical composition of oxide ore was determined by analysis on a dry basis and must be the variable of greatest significance in the gold recovery for this research, is the concentration of solution of thiourea and citric acid, reaching an gold recovery of 62% and growing trend. It was shown that by increasing the concentration of thiourea at acidic pH, controlled with citric acid, the amount of oxidized gold mining ore